NEW DATA ON INFLUENCE OF PREBIOTICS ON MORBIDITY OF INFANTS - A.V. Surzhik ("Paediatrician" Publishers LLC, 2009)
The article presents new data on positive effect of prebiotical complex on immune system. The decrease of mortality with as intestinal infections, as infections of upper airways was shown on the basis of nutrition with milk compound, fortified with prebiotics.Key words: infants, adapted milk compounds, prebiotics, immunity, infections.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):117-122)